Communication and Negotiation of the Village Consultative Body in the Development Program Formulation in the Parado Sub-District, Bima Regency - Khairatun Hisan; Arifuddin Tike; Kamaluddin Tajibu (Jurnal Mercusuar, 2023)
This research discusses the communication and negotiation of the Village Consultative Body (BPD) in the development program formulation in Parado District, Bima Regency. The research is qualitative in nature with sociological and communication approaches. Data sources include village government, BPD, community leaders, youth leaders, and documents such as annual reports and online news. Data collection methods involve observation, interviews, and documentation. Data processing and analysis are conducted through stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that BPD negotiations, particularly in village forums (musdus) and APBDes meetings, tend to be dominated by collaborative negotiations prioritizing openness and solutions beneficial to all parties, although sometimes accommodating limitations in funding and time. Supporting factors for communication include thorough planning, aligned interests, and the availability of facilities and infrastructure. The implication of this research is to provide information for the community to mitigate the risks of unbeneficial development programs and to provide insights into supporting and inhibiting factors in formulating development programs beneficial to all parties.